Kinematic Analysis of Parallel Mechanism for Multi-link Suspension - Jiang Mao; Xiaofei Zhu; Licheng Li (Jixie chuandong)
Parallel mechanism has the advantages of large stiffness，fast response and high precision， which is suitable for suspension field. A new type of parallel mechanism for automobile multi-link suspension is proposed， the kinematic model of the mechanism is established， combined with the screw theory， the spatial motion characteristics of the mechanism are analyzed through the pose parameters， and the screw amount representing the motion is approximately even. Combined with the kinematics concept of the automobile suspension， the wheel positioning parameters are given using the homogeneous transformation matrix. The instantaneous kinematic analysis method of the suspension is proposed using the screw theory.